Media Pembelajaran Pobiqobra Berbasis Blended Learning untuk Meningkatan Motivasi dan Hasil Belajar Siswa MAN 3 Jombang - M. Tholib (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2022)
This study aims to describe the impact of the application of blended learning-based "Pobiqobra" media on students' motivation and mathematics learning outcomes at MAN 3 Jombang.. The learning media "Pobiqobra" is applied by combining direct face-to-face learning combined with online learning, namely by using powerpoint media, learning blogs, quipper and short geogebra with "Pobiqobra". This study used descriptive qualitative method. The research subjects were students of class XI MIPA 4 at MA Negeri 3 Jombang, totaling 35 people. This research instrument uses a questionnaire and the data collected is analyzed qualitatively. The results of this study indicate that there is a positive impact on the high motivation and learning outcomes of students by applying the Pobiqobra learning media. The results of student questionnaire analysis on learning Mathematics are 86% of students feel happy and 98% say the learning media used is very effective and satisfying.